Emerging Technologies in Vocational Education and Training - Ghosh, Lisa; Ravichandran, R. (MO.RI Publishing, 2024)
This study explores into the dynamic landscape of vocational education, spotlighting the pivotal role played by emerging technologies in shaping pedagogy and skill development. The swiftly changing world of work demands educational adaptability, and emerging technologies offer innovative avenues to meet this imperative. Examining cutting-edge innovations such as Virtual Reality (VR), Augmented Reality (AR), Artificial Intelligence (AI), Machine Learning (ML), Internet of Things (IoT), Robotics, Automation, Big Data, Analytics, Blockchain, 3D printing, and Gamification, this research explores their application in vocational education. Drawing on a comprehensive literature review and diverse global case studies, the paper explores the transformative potential of these technologies and associated challenges. Despite cost and training concerns, the study suggests solutions like affordable access, educator training programs, and equitable technology distribution. It concludes by underscoring the necessity for strategic investments in professional development, technology accessibility, and inclusive educational programs to ensure responsible integration of emerging technologies, positioning vocational education as a catalyst for societal and economic advancement.